Variety of size and form of GRM2 bacterial microcompartment particles - Cesle, Eva Emilija; Filimonenko, Anatolij; Tars, Kaspars; Kalnins, Gints (Protein science, 2021)
Bacterial microcompartments (BMCs) are bacterial organelles involved in enzymatic processes, such as carbon fixation, choline, ethanolamine and propanediol degradation, and others. Formed of a semi‐permeable protein shell and an enzymatic core, they can enhance enzyme performance and protect the cell from harmful intermediates. With the ability to encapsulate non‐native enzymes, BMCs show high potential for applied use. For this goal, a detailed look into shell form variability is significant to predict shell adaptability. Here we present four novel 3D cryo‐EM maps of recombinant Klebsiella pneumoniae GRM2 BMC shell particles with the resolution in range of 9 to 22 Å and nine novel 2D classes corresponding to discrete BMC shell forms. These structures reveal icosahedral, elongated, oblate, multi‐layered and polyhedral traits of BMCs, indicating considerable variation in size and form as well as adaptability during shell formation processes.